2015
DOI: 10.1902/jop.2014.140373
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Platelet‐Rich Plasma and Other Plasma Preparations Against Periodontal Pathogens

Abstract: PRP expressed antibacterial properties, which may be attributed to platelets possessing additional antimicrobial molecules. The application of PRP on periodontal surgical sites is advisable because of its regenerative potential and its antibacterial effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
61
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 39 publications
3
61
0
2
Order By: Relevance
“…The authors found that all plasma preparations can inhibit bacterial growth, with PRP showing the superior activity. In the current study, the activity of PRP against A. actinomycetemcomitans and P. gingivalis is comparable to that of Yang et al (2015). These results confirm the beneficial role of PRP in the treatment of periodontal disease.…”
Section: Discussionsupporting
confidence: 84%
“…The authors found that all plasma preparations can inhibit bacterial growth, with PRP showing the superior activity. In the current study, the activity of PRP against A. actinomycetemcomitans and P. gingivalis is comparable to that of Yang et al (2015). These results confirm the beneficial role of PRP in the treatment of periodontal disease.…”
Section: Discussionsupporting
confidence: 84%
“…Anitua et al[61] demonstrated that even if an additional dose of leukocytes was present it did not significantly enhance the antimicrobial properties of PRP. Yang et al[108] (2015) in a study evaluated the antimicrobial activity of four plasma preperations: PRP, platelet poor plasma (PPP), platelet depleted plasma (PDP) and PRF. Using haemocytometer, they found leucocytes only in PRP and not in other preparations.…”
Section: Discussionmentioning
confidence: 99%
“…However, one should note that the technique of PRF preparation was not according to the L-PRF protocol given by Choukroun et al[22] in 2000. To make PRF, Yang et al[108] used fraction of PRP and activated it by 23 mmol/L of calcium chloride for 30 min and centrifuged again at 6000 g for 30 min to recover “fibrin-free supernatant” which they labeled as PRF. Hence, although their experiment highlighted the antimicrobial effect of plasma, regardless of platelet and leukocyte concentration, their conclusion of PRF should be read with caution.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the article by Yang et al 1 We would like to commend the authors for exploring for the first time the antibacterial aspect of platelet‐rich plasma and other plasma preparations. Our concern was regarding the protocol followed for preparation of plasma‐rich fibrin (PRF), which according to authors was in accordance with a modified method of Kawazoe and Kim 2 .…”
mentioning
confidence: 99%